EFEKTIVITAS MODEL PBL BERBANTUAN PAPAN JEJAK PEMBAGIAN TERHADAP PRESTASI BELAJAR MATEMATIKA KELAS IV - Rika Riski Pratiwi; Butsi Prihastari, Ema; Irmade , Oka (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The study aimed to analyse the effectiveness of the use of the PBL model with the help of the division trace board which is expected to also have the potential to improve the learning achievement of fourth grade students for mathematics lessons so that student learning outcomes can reach the Criteria for Achievement of Learning Objectives (KKTP). Quantitative approach was used in this study, the type of quasi experimental design and the form of nonequivalent control group design. The total sampling technique was used in determining the sample, to collect data the techniques were classroom observation, tests and documentation. The tests used to analyse the data were normality, homogeneity, independent sample T-test and N-gain test. The acquisition of t-test hypothesis data resulted in Sig. (2-tailed) is 0.003 <0.05 and the N-gain test of the experimental class average is superior to the control class. It is shown from the N-gain percent of 76.36 experimental class then 55.98 control class which means that the hypothesis analysis rejects Ho and accepts Ha. So it is concluded that there is an effectiveness of using the problem-based learning model aided by the division trace board on the mathematics learning achievement of class IV SD Nayu Surakarta in the 2024/2025 academic year.